Alternative dry cow management strategy - Aranha Gamarra, Caio (Kansas State University, 2020)
Poor transition from late gestation to early lactation influences postpartum performance of lactating dairy cows. Considering that increased vaginal temperature (VT) before calving is associated with reduced postpartum performance during summer, this thesis focused on investigating a novel management strategy in the dry period to improve postpartum performance during summer of cows with high temperature (HT) in late gestation. This study was conducted in three commercial dairy herds in the High Plains region during summer. Vaginal temperature was assessed from 1,603 multiparous Holstein cows with 236 to 250 of gestation, and the top 20% highest temperature were classified as HT cows. High temperature cows were randomly assigned as treatment or control. Treatment consisted of moving cows earlier to the close-up pen compared with the rest of the herd. Therefore, three groups were compared in the study: high temperature and extended days in the close-up pen (HT-TRT), high temperature and not extended days in the close-up pen (HT-CON), and low temperature and not extended days in the close-up pen (LT). Cows were followed until 90 days in milk (DIM) of the next lactation to compare postpartum performance. In a cohort of cows (n = 201), blood sample was collected at VT assessment to compare pregnancy-associated glycoprotein (PAG) concentration of HT and LT cows. Days spent in the close-up pen differed among treatments (HT-TRT = 24.5 ± 1.8; HT-CON = 15.9 ± 1.8; LT = 20.3 ± 1.8). Low temperature cows had longer gestation length and decreased percentage of twinning compared with HT-CON and HT-TRT cows. Low temperature cows had and tended to have decreased percentage of stillbirth than HT-CON and HT-TRT, respectively. In addition, LT cows had decreased percentage of uterine disease in the first 21 DIM than HT-CON cows. Nonetheless, LT and HT-TRT did not differ in percentage of cows diagnosed with uterine disease. High temperature control cows had reduced percentage of cows pregnant at first service compared with LT cows, however, no difference was detected between LT and HT-TRT cows. Pregnancy-associated glycoprotein concentration at VT assessment differed between HT and LT cows. Cows with increased VT in late gestation benefited from spending more days in the close-up pen during summer months. Differences in PAG concentrations of LT and HT cows suggest that PAG could be a potential maker to identify cows that will have postpartum problems after calving during summer months.
Keywords: Dairy cow; Heat stress; Dry period; Postpartum performance; Prepartum; Dairy cow health